The Effect Of Effleurage Massage With Lemon Aromatherapy On Reducing Primary Dysminorea Pain In Adolescent Females At Al-Hijrah Sirah Senior High School, Pulau Padang, Ogan Komering Ilir Regency - Eri Puji Kumalasari; Liswani (Journal for Research in Public Health, 2026)
Dysmenorrhea is menstrual pain and is the most common gynecological problem in women of reproductive age. Management of dysmenorrhea can be done pharmacologically and non-pharmacologically. Pharmacological therapy includes administration of analgesic drugs, hormonal therapy, non-steroidal prostaglandin drugs, and cervical canal dilation. While non-pharmacological therapy through acupressure, yoga, warm or cold compresses, exercise, drinking herbal medicine, massage, rest, knee chest position, breathing relaxation techniques. Effleurage massage is a massage technique that is done to help speed up the pain recovery process by using hand touch to create a relaxing effect. Lemon The fragrant compound limonene has effects, anxiety, analgesics and sedatives that can inhibit prostaglandin activity and reduce pain. The purpose of this study was to determine the effect of effleurage massage with lemon aromatherapy on reducing primary dysmenorrhea pain in adolescent girls. This study population is all adolescents with primary dysmenorrhea who meet the inclusion and exclusion criteria with a sample size of 14 respondents using a one group pretest posttest only research design. The collected data were then analyzed using the chi square statistical test (p value = 0.000), based on the chi square analysis showed that effleurage massage with lemon aromatherapy has an effect on overcoming primary dysmenorrhea in adolescent girls.